Universal definition and classification of heart failure: a report of the Heart Failure Society of America, Heart Failure Association of the European Society of Cardiology, Japanese Heart Failure Society and Writing Committee of the Universal Definition of Heart Failure: Endorsed by the Canadian Heart Failure Society, Heart Failure Association of India, Cardiac Society of Australia and New Zealand, and Chinese Heart Failure Association. (3rd March 2021) - Bozkurt, Biykem; Coats, Andrew J.S.; Tsutsui, Hiroyuki; Abdelhamid, Ca Magdy; Adamopoulos, Stamatis; Albert, Nancy; Anker, Stefan D.; Atherton, John; Böhm, Michael; Butler, Javed; Drazner, Mark H.; Michael Felker, G.; et al.
Abstract: In this document, we propose a universal definition of heart failure (HF) as a clinical syndrome with symptoms and/or signs caused by a structural and/or functional cardiac abnormality and corroborated by elevated natriuretic peptide levels and/or objective evidence of pulmonary or systemic congestion. We also propose revised stages of HF as: At risk for HF (Stage A), Pre‐HF (Stage B), Symptomatic HF (Stage C) and Advanced HF (Stage D). Finally, we propose a new and revised classification of HF according to left ventricular ejection fraction (LVEF). This includes HF with reduced ejection fraction (HFrEF): symptomatic HF with LVEF ≤40%; HF with mildly reduced ejection fraction (HFmrEF): symptomatic HF with LVEF 41–49%; HF with preserved ejection fraction (HFpEF): symptomatic HF with LVEF ≥50%; and HF with improved ejection fraction (HFimpEF): symptomatic HF with a baseline LVEF ≤40%, a ≥10 point increase from baseline LVEF, and a second measurement of LVEF > 40%.